Teaching English towards the Hearing-Impaired Students - Antonius Setyawan (Journal of English Language Teaching and Islamic Integration, 2020)
The  EFL  teaching  is  challenging.  Moreover,  teaching English  towards  the  hearing-impaired  students  (hereafter  HIS)  must have  its  own  uniqueness  because  of  the  greater  challenges.  The exploration  in  this  phenomenological  study  goes  with  the  teacher’s lived  experience  in  teaching  English  especially  vocabulary  towards the  HIS.  Telling  narratively  of  the  teacher’s  lived  experience  in teaching English towards the HIS is the purpose of this research. The descriptions  go  on  the  teacher’s  understanding,  belief,  feeling, intention,  and  action  which  are  elaborated  by  the  purpose  of  the teaching, the materials, the technique, and the achievement. According to the findings, the purposes of teaching vocabulary are to enrich their vocabulary mastery and to proof that the HIS can learn language. The teacher can only teach simple words because it takes time and lots of efforts. Visualization  is the best teaching technique ever  for the HIS because it helps better memorization since it gives emotional feeling for  them.  In  conclusion,  the  HIS  can  learn  simple  vocabulary. Visualization helps them memorizing words better.